Mental wellbeing and its relationship to happiness of the university students - MuneerMsehirAlani ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
Mental well-being is described as a mixture of the individual’s experience and his ability to work as an individual and as a member of society, and it can be said that it is a good feeling, and the researcher believes that many variables affect mental well-being, including happiness, as it is defined as a feeling of contentment, satisfaction, self-assurance, and self-fulfillment. : 1- The mental well-being of university students. 2- Differences in mental well-being of university students according to specialization (scientific, humanistic). 3- Happiness among university students. 4- Differences in happiness among university students according to the variable of specialization (scientific, humanistic) 5- The extent to which happiness contributes to the mental well-being of university students. The research was limited to students in the morning initial studies from Anbar University for the academic year (2018-2019), as the size of the research sample reached (100) students. To achieve the goals of the current research, the researcher extracted the statistical characteristics of the two standards (the distinction and difficulty of the paragraphs, the honesty and the stability of the two standards). After analyzing the data using the appropriate statistical means, the current research concluded the following results: 1- Anbar University students are characterized by mental well-being. 2- There are differences of significant significance according to the variable of specialization and in favor of human specialization. 3- Anbar University students enjoy happiness. 4- There are significant differences in the specialty variable in favor of the human specialty. 5- There is a contribution to happiness in mental well-being.